P03 A systematic review of interventions in community infrastructure (places and spaces) to boost social relations and community wellbeing. (3rd September 2019) - Bagnall, AM; South, J; Southby, K; Di Martino, S; Pilkington, G; Mitchell, B; Pennington, A; Corcoran, R
Abstract : Background: Stakeholder engagement for the What Works Centre for Wellbeing's (WWCW) Community Wellbeing Evidence Programme identified 'boosting social relations' in communities as a priority policy-related topic. A scoping review of 34 reviews identified evidence gaps relating to social relations in the following areas: community infrastructure (places and spaces); interventions to reduce or prevent social isolation in adults <60 years; community engagement and volunteering; social network analyses. We developed 'community infrastructure (places and spaces)' as a systematic review, as this can be addressed at a local or regional level and has potential to produce immediate practical impact. Methods: We searched 11 bibliographic databases from 1997–2017, performed reference and citation checking, searched the websites of relevant organisations, and issued a call for evidence through the WWCW. We included studies which reported: interventions to improve or make alternative use of physical places and spaces at community or neighbourhood level; outcomes of social relations, community wellbeing and related concepts; quantitative, qualitative and mixed methods studies, and process evaluations. Two reviewers undertook study selection. One reviewer undertook data extraction and validity assessment, with a random 20% checked by a second reviewer. Validity of included studies was assessed using established checklists. Following thematic synthesis of qualitative data, a narrative synthesis was produced for each of eight intervention categories. The GRADE and CERQual approaches were used to rate the overall strength of evidence for each outcome. Results: 51 studies, mostly of poor to moderate quality, were included. The better quality evidence was qualitative, and most of the review's findings come from the thematic synthesis of qualitative evidence There was moderate evidence that Community hubs may promote social cohesion, increase social capital and build trust between people, widen social networks and increase interaction between people, and increase people's knowledge or skills; Changes to neighbourhood design may positively affect sense of belonging and pride in a community; Green and blue space interventions that provide the opportunity to participate in activities or meetings improve social interactions, increase social networks, bonding and bridging social capital, physical activity and healthy eating, and improve people's skills and knowledge. There were also common themes relating to facilitators and barriers to successful interventions. Conclusion: The review found moderate evidence that a range of intervention approaches to community infrastructure can boost social relations and community wellbeing. Future research should prioritise high quality evaluations using repeated measures and validated tools, with robust and credible qualitative evidence.